Rice productivity in Myanmar: Assessment of the 2025 dry season and outlook for the 2025 monsoon - Aung, Zin Wai; Minten, Bart (International Food Policy Research Institute, 2025)
We analyze paddy rice productivity and profitability for the 2024 and 2025 dry seasons, using data from the Myanmar Agriculture Performance Survey (MAPS), conducted between August 11 to October 26, 2025. The survey covered plots managed by 872 paddy producers.